Comparative Study of Cultural Content Integration in English Teaching Materials for High School Students in Indonesia and the Philippines - Muhsinin, Muhsinin; Chua, Bernardo U; Assapari, Muhammad Mugni (JOLLT Journal of Languages and Language Teaching, 2025)
This study investigates the incorporation of cultural information in English teaching materials utilised in high schools in Indonesia and the Philippines. This research utilises a qualitative content analysis methodology to assess two textbooks: Bahasa Inggris English for Change (Indonesia) and Oral Communication in Context for Senior High School (Philippines). The analysis employs Cortazzi and Jin’s cultural content categories (source, target, international culture) alongside Adaskou, Britten, and Fahsi's four dimensions of culture (aesthetic, sociological, semantic, pragmatic). The findings indicate a common focus on local (source) culture, substantial representation of English- speaking nations (target culture), and initiatives to incorporate worldwide viewpoints. Nevertheless, there are notable differences in the methodologies and thematic emphasis that reflect specific sociocultural situations. The study emphasises the significance of culturally responsive pedagogy and provides recommendations for curriculum developers to enhance intercultural competency in English language instruction.